Kinetics Behaviour of Hydrates Drilling Muds - Lal, B. (Springer Nature, 2022)
In this section, the kinetics data for almost the drilling mud tested for kinetically managing hydrate formation and dissociation in hydrate sediment wellbore are reviewed and discussed. The data provided in this section provides fundamental information on the effect of drilling mud additives on the kinetics of hydrates formation and dissociation in the presence of hydrate different hydrate formers. Â© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.